2018
DOI: 10.1016/j.pedneo.2017.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral propranolol on periocular Capillary Hemangiomas of Infancy

Abstract: Oral propranolol is highly effective and safe in the treatment of periocular capillary hemangiomas in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…12 Leaute-Labreze in 2008, incidentally found that oral propranolol has an excellent role in treatment of infantile haemangioma, while they were treating pediatric cardiac patients. 5,8,14 Since then Systemic propranolol is a new treatment modality for infantile haemangioma. In our study, age of the patient ranged from 1-42 months (mean 5.8 months).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12 Leaute-Labreze in 2008, incidentally found that oral propranolol has an excellent role in treatment of infantile haemangioma, while they were treating pediatric cardiac patients. 5,8,14 Since then Systemic propranolol is a new treatment modality for infantile haemangioma. In our study, age of the patient ranged from 1-42 months (mean 5.8 months).…”
Section: Discussionmentioning
confidence: 99%
“…Infantile capillary haemangioma is considered a hamartoma and represents one of the most common benign vascular tumour in children. 3,8,10,11 This lesion may noticed at birth as a reddish spot (30-35%) or develops a few weeks after birth 5 that enlarges during first months of life, and then maintains its size or involutes (50%) at fifth year of age. 10 The female to male ratio is 3:1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently available treatments include: systemic use of β-blockers, corticosteroids, interferon α, vincristine, angiotensin-converting enzyme blockers, as well as topical β-blockers, corticosteroids, imiquimod, injection of corticosteroids [5,17]. Among these methods, the most studied are systemic treatment and topical application of β-blockers, which have shown good results [18,19]. Other local treatments include: laser therapy (dye lasers, neodymium laser, argon and CO 2 laser), surgical removal, embolization and compression therapy [20][21][22].…”
Section: Suggested Solution To the Problemmentioning
confidence: 99%